Mechanisms of biological processes in domestic wastewater treatment plants = Mechanizmy procesów biologicznych w przydomowych oczyszczalniach ścieków - Myszograj, Sylwia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The growing demand for solutions of household sewage treatment plants means that many new or improved technological solutions are available on the market. The implementation of these technologies is associated with the need to known the mechanisms of the unitary biological processes occurring when removing organic carbon, nitrogen and phosphorus from wastewater. Determining the optimal conditions for these processes will determine the correct operation of the household sewage treatment plant.
Keywords: wastewater; organic carbon; nitrogen; phosphorus; biochemical processes; węgiel organiczny; ścieki; azot; fosfor; procesy biochemiczne